PENGARUH HARGA EMAS DUNIA, RATA-RATA INDUSTRI DOW JONES, DAN INDEKS SHANGHAI TERHADAP INDEKS HARGA SAHAM GABUNGAN PERIODE 2017-2021 - Sulaksana Adi; Linna Ismawati (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
The purpose of this study is to see the influence of the World Gold Price, Dow Jones Industrial Average and Shanghai Stock Exchange either partially or simultaneously on the Indonesia Composite Stock Price Index and to determine the development of each variable in the January 2017-December 2021 period The research method used is descriptive and verification methods with a quantitative approach. Meanwhile, the data used is secondary data which includes data on the World Gold Price, Dow Jones Industrial Average, Shanghai Stock Exchange, and the Indonesia Composite Stock Price Index. The design of analysis used are multiple regression analysis, classic assumption test, correlation coefficient analysis and coefficient of determination analysis. And for hypothesis testing using the T test and F test with the SPSS v22 application program. The results showed that partially the World Gold Price has an effect on the Indonesia Composite Stock Price Index. The Dow Jones Industrial Average has an effect on the Indonesia Composite Stock Price Index. The Shanghai Stock Exchange has no effect on the Indonesia Composite Stock Price. And simultaneously the World Gold Price, Dow Jones Industrial Average, and Shanghai Stock Exchange have an effect on the Indonesia Composite Stock Price Index.